Penyuluhan Tentang Imunisasi Dasar Lengkap Pada Ibu Balita : Counseling about complete basic immunization for mothers of toddlers - Masulilli, Fitria; Jurana, Jurana; Irsanty, Collein; Pangaribuan, Helena; Baiq Emy, Nurmalisa; Supirno, Supirno; Ayu, Sri Manika; Marlin, Marlin (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2023)
Introduction Complete national routine immunization coverage is currently slowly increasing again after the COVID pandemic from 84% in 2019 to 94.9% in 2022. Indonesian children have been immunized. This increase was given a good score but not enough, because there are still around 5% or 240,000 Indonesian children who have not received additional protection from complete basic immunization, meaning these children are still at high risk of contracting diseases that can be prevented by immunization (PD3I). The Ministry of Health targets 100 percent of babies to receive complete basic immunization (IDL) by 2023. This community service aims to provide knowledge to mothers of toddlers about complete basic immunization (0 to 11 months). This service method takes the form of counseling and giving leaflets to mothers of toddlers. This community service activity was carried out at Latulip Posyandu, Layana Village, Talise Health Center working area on June 21 2023. The target audience for this community service activity was all mothers with toddlers who live in Layana Village as the Talise Health Center Working Area, 18 mothers of toddlers. The results of the activity were the knowledge of mothers of toddlers about complete basic immunization after counseling, namely the majority with good knowledge, 15 participants (83.3%) and 3 participants (16.7%) with sufficient knowledge. The conclusion is that this community service activity can provide understanding to mothers of toddlers about complete basic immunization. Suggestions to the Talise Community Health Center to continue to increase community knowledge and provide motivation for mothers of toddlers to support the success of achieving complete basic immunization coverage according to the national target of 100 percent.